2017
DOI: 10.1007/s13398-017-0412-9
|View full text |Cite
|
Sign up to set email alerts
|

Tsirelson-like spaces and complexity of classes of Banach spaces

Abstract: ABSTRACT. Employing a construction of Tsirelson-like spaces due to Argyros and Deliyanni, we show that the class of all Banach spaces which are isomorphic to a subspace of c 0 is a complete analytic set with respect to the Effros Borel structure of separable Banach spaces. Moreover, the classes of all separable spaces with the Schur property and of all separable spaces with the DunfordPettis property are Π 1 2 -complete.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…As noticed in [13], we obtain immediately that the class of isomorphic subspaces of c 0 is not Borel (that is the mentioned result from [20]), as the intersection of this class with the Borel class of all infinite-dimensional separable L ∞ -spaces is exactly the isomorphism class of c 0 (see [18,Corollary 1]). This works in one direction only.…”
Section: Introduction and The Main Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…As noticed in [13], we obtain immediately that the class of isomorphic subspaces of c 0 is not Borel (that is the mentioned result from [20]), as the intersection of this class with the Borel class of all infinite-dimensional separable L ∞ -spaces is exactly the isomorphism class of c 0 (see [18,Corollary 1]). This works in one direction only.…”
Section: Introduction and The Main Resultsmentioning
confidence: 61%
“…Godefroy asked in [13] if the isomorphism class of the space c 0 is Borel. In the preceding paper [20], we have found a partial solution, proving that the class of all spaces isomorphic to a subspace of c 0 is not Borel. The main result of the present work is a full solution of Godefroy's problem.…”
Section: Introduction and The Main Resultsmentioning
confidence: 92%
“…is also analytic. This is because a Suslin operation of analytic sets is an analytic set (see, e.g., [ We now show that the class is R ∩ As c 0 is not analytic and hence by Suslin's theorem (see, e.g., [ [25] also provides a proof of the fact that R ∩ As c 0 is not Borel. b) It also follows easily from [32, Theorem 1.2] that given 1 < p < ∞ the class of all separable reflexive spaces that are asymptotic ℓ p is analytic.…”
Section: Final Remarks and Open Problemsmentioning
confidence: 84%
“…. Now for T ∈ Tr(2 × N), we define the space E T to be the completion of c 00 (2 <N \ {∅}) with respect to the norm Here, for a compact set M ⊂ 2 N , · M denotes the Tsirelson space T * [M, 1/2] as defined in [19]. Kurka showed that there exist Borel maps S, S * : Tr(2 × N) → SB such that for each T ∈ Tr(2 × N), S(T ) is isometric to E T and S * (T ) is isometric to E * T .…”
Section: We Letmentioning
confidence: 99%